New Two Simple Sinusoidal Generators with Four 45o Phase Shifted Voltage Outputs Using Single FDCCII and Grounded Components - Kasim K. Abdalla (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Two new 45o phase shifted sinusoidal oscillator configurations employing single Second Generation Fully Differential Current Conveyor (FDCCII), two grounded capacitors and two grounded resistors are presented. The proposed oscillators can provide four sinusoidal voltage outputs with each a 45o phase difference. These circuits can also be utilized as voltage-mode quadrature oscillators. Additional output stages incorporation in FDCCII can also result in current outputs spaced 45 degree apart. The proposed circuits enjoy the simplicity and less passive and active component. The Total Harmonic Distortion (THD) of the output waveforms was reasonability values (less than 4.5%). The circuits can supply two equi-quadrature outputs and the Lissajous patterns confirm the quadrature voltage output waveforms. The workability of the circuits is simulated by PSPICE 0.18 μm CMOS technology. The non-ideal analysis and simulation results verifying theoretical analyses are also investigated.